1986
DOI: 10.1038/bjc.1986.108
|View full text |Cite
|
Sign up to set email alerts
|

DNA measurement – An objective predictor of response to irradiation? A review of 24 squamous cell carcinomas of the oral cavity

Abstract: Summary DNA measurements on biopsy material from 24 squamous cell carcinomas of the oral cavity given preoperative radiotherapy indicate that DNA aneuploid tumours respond better to radiotherapy than do diploid and polyploid tumours. The mean S-phase value was higher (16.1%) for 8 tumours that were eradicated by preoperative radiotherapy than for 13 that did not respond (8.1%). These factors correlated better with the response than did histological and clinical (T) classifications.DNA-ploidy and S-phase estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

1989
1989
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 12 publications
0
9
1
1
Order By: Relevance
“…Twenty-five of these tumours were aneuploid, three were diploid. The potential doubling time of aneuploid tumours was significantly less than that of diploid tumours which may explain the observation that aneuploid tumours are often more responsive to therapy (Franzen et al, 1986;Barlogie et al, 1987;Guo et al, 1989). We have previously reported that in advanced unresectable squamous carcinoma of the head and neck there was a significant prolongation of survival in patients with aneuploid tumours compared with patients with diploid tumours when treated with cisplatin (Cooke et al, 1990).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Twenty-five of these tumours were aneuploid, three were diploid. The potential doubling time of aneuploid tumours was significantly less than that of diploid tumours which may explain the observation that aneuploid tumours are often more responsive to therapy (Franzen et al, 1986;Barlogie et al, 1987;Guo et al, 1989). We have previously reported that in advanced unresectable squamous carcinoma of the head and neck there was a significant prolongation of survival in patients with aneuploid tumours compared with patients with diploid tumours when treated with cisplatin (Cooke et al, 1990).…”
Section: Discussionmentioning
confidence: 83%
“…The method developed by Begg et al (1985) (Friedlander et al, 1984;Volm et al, 1985) including some head and neck tumours (Holm, 1982;Franzen et al, 1986) 11.5 7.9 14.8 P<0.01 (2.6-30.0) (2.6-14.7) (7.6-30.0) in breast cancer where high TLI correlates with reduced survival (Meyer & Hixon, 1979;Gentili et al, 1981) and may also predict tumour radio and chemosensitivity (Silvestrini et al, 1984). The relationship between TLI and prognosis is not so well established in head and neck cancer where unlike in breast cancer the median TLI fails to divide patients into two groups with significantly different outlook (Courdi et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that Sphase fraction was of high prognostic significance, particularly in breast cancers, non-Hodgkin's lymphomas, ovarian cancers, neuroblastoma, bladder and lung cancers. It is not clear whether they attempted a comprehensive review of all publications up to 1988 when the manuscript was submitted, but within the head and neck region they omitted the paper by Franzen et al (1986). Despite Tubiana and Courdi's strong conclusion on the prognostic usefulness of SPF there have been subsequent large series in both breast and ovarian cancer which found no correlation between SPF and prognosis (Conte et al, 1989;Cooke et al, 1992).…”
Section: Statisticsmentioning
confidence: 99%
“…Ensley et al (1989) reported that three-quarters of 165 patients with squamous carcinomas of the head and neck had an S-phase fraction (SPF) above 15% and that there was a strong direct correlation between DNA index and SPF. Franzen et al (1986) found a mean SPF of 6.4% in diploid tumours, 10% in polyploid tumours and 19% in aneuploid tumours, with a range of 1-30% amongst 24 oral cavity carcinomas. Johnson et al (1985) reported a mean SPF of 19% with a range of 4-45% in 45 patients with tumours at various sites within the head and neck.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation